Population structure and gene flow in stomion: A species swarm of flightless beetles of the galápagos islands - Finston, T.L. (Terrie L.); Peck, S. (Stewart) (Heredity, 1995)
Stomion is a swarm of 13 flightless tenebrionid beetle species endemic to the Galápagos Islands. Their distribution is patchy and largely restricted to the littoral and arid zones of the archipelago. Each taxon is found on one or a few geographically close islands. Thirty-five populations representing nine of the taxa were examined at eight polymorphic enzyme loci using cellulose acetate electrophoresis to measure patterns of gene flow and investigate models of dispersal in a relatively young species group exhibiting spatially isolated populations. Genetic subdivision is high, particularly among populations of taxa which inhabit more than one island, revealing restricted gene flow and confirming the high potential for reproductive isolation among subpopulations. The mean FST across taxa was 0.30. The genetic differentiation occurring between spatially isolated populations may explain the exuberant speciation of the genus in the Galápagos. Tests of gene flow models give support to the stepping-stone model of dispersal. Because of their lack of flight wings, interisland dispersal of Stomion probably occurred by oceanic drift as pleuston or on floating debris, with individuals colonizing nearby islands more frequently than ones at a greater distance.